1992
DOI: 10.1182/blood.v80.7.1666.1666
|View full text |Cite
|
Sign up to set email alerts
|

Low-risk intensive therapy for multiple myeloma with combined autologous bone marrow and blood stem cell support

Abstract: To improve the safety of autotransplantation for myeloma, peripheral blood stem cell (PBSC) collection was attempted in 75 previously treated patients after the administration of high-dose cyclophosphamide (HD-CTX; 6 g/m2) with or without granulocyte-macrophage colony- stimulating factor (GM-CSF). Sixty patients subsequently received melphalan 200 mg/m2 (57 patients) or melphalan 140 mg/m2 and total body irradiation (850 cGy) (3 patients) supported by both autologous bone marrow and PBSC; 38 patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…The median survival of our patients younger than 40 years who had normal renal function or low serum 2 -microglobulin levels was about 8 years. This long survival in young patients with MM treated with conventional chemotherapy should be considered when evaluating the results in patients receiving more intensive therapy such as bone marrow transplantation (Gahrton et al, 1991;Attal et al, 1992;Harousseau et al, 1992;Jagannath et al, 1992). Patients who also have a low plasma cell labelling index might have an even longer median survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median survival of our patients younger than 40 years who had normal renal function or low serum 2 -microglobulin levels was about 8 years. This long survival in young patients with MM treated with conventional chemotherapy should be considered when evaluating the results in patients receiving more intensive therapy such as bone marrow transplantation (Gahrton et al, 1991;Attal et al, 1992;Harousseau et al, 1992;Jagannath et al, 1992). Patients who also have a low plasma cell labelling index might have an even longer median survival.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of chemotherapy in MM is palliative and does not usually result in long-lasting responses, even when intensive regimens such as VAD or high-dose melphalan are used (Gore et al, 1989;Samson et al, 1989;Lokhorst et al, 1992). For this reason, the efficacy of high-dose therapy followed by autologous or allogeneic stem cell support is currently being investigated (Gahrton et al, 1991;Attal et al, 1992;Harousseau et al, 1992;Jagannath et al, 1992;Alexanian & Dimopoulos, 1994). Although a median survival of 54 months is the longest reported so far in long-term studies of MM, it is still unsatisfactory, especially in persons younger than 40 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Response to conventional chemotherapy should include either patients achieving the plateau phase or combine both objective and partial or minimal response. The high complete response rate currently obtained with high-dose therapy followed by autologous bone marrow or peripheral stem cell rescue is encouraging (Jagannath et al, 1992: Attal et al, 1992: Harousseau et al, 1992. However, longer follow-up is required to establish the actual impact of this high tumour reduction on survival.…”
Section: Discussionmentioning
confidence: 99%
“…The standard melphalan dose in single agent HDM therapy for myeloma is a body surface area (BSA) based dose of 200 mg m -2 , used initially in Arkansas [11], and confirmed by Moreau et al [12] where improved OS was observed for patients receiving 200 mg m -2 compared with melphalan 140 mg m -2 and total body irradiation. Subsequent trials have used 200 mg m -2 as a standard [13][14][15] and comparison of 200 mg m -2 with 100 mg m -2 demonstrated better outcomes with the higher dose in the tandem transplant setting [16].…”
Section: Introductionmentioning
confidence: 99%